Menguak Penyakit Turunan pada Manusia - Anjani, Arum Dwi; Aulia, Devy Lestari Nurul; Rani, Aulia (VISA: Journal of Vision and Ideas, 2024)
Genetic disorders, also known as genetic diseases, are conditions caused by abnormalities in one or more genes that cause a clinical phenotype. Inheritance patterns of certain traits are passed down to human offspring, with some traits being detrimental and not being detrimental (normal). Hereditary diseases are conditions caused by abnormalities in one or more genes that result in a specific clinical phenotype.